FINANCING MANAGEMENT OF MIDDLE EDUCATION ASSISTANCE FUNDS DURING THE PANDEMIC - Sri Mulyati; Sundaniawati Safitri (Universitas Nurul Jadid, 2021)
This study aimed to explore funding management of School Operational Assistance Funds (Indonesian term: Bantuan Operasional Sekolah) during COVID-19 Pandemic at Al-Muhajirin Islamic Junior High School, Gunungsindur, Bogor. This study employed a descriptive qualitative approach by utilizing interviews, documentation, and observation to collect the data. The data analysis process involved a series of procedures from data collection, data reduction, data presentation, data verification to conclusions. The results showed that the fund management at Al-Muhajirin Islamic Junior High School was actualised into planning, implementing, and supervising stages. Planning includes the activities of formulating a draft budget. The implementation stage was through socialization and distribution of funds. The supervision stage involves all school parties, both internal and external. Fund reporting is carried out via offline and online pathway every semester.